The structure of the beginning in the poetry of the poet Badr Shaker AI- Sayyab (an artistic Study) (Journal of Imam Al-Kadhim College, 2023)
The first concern of the composer of the poem is the initiation because he controls the beginning of the composition of the poem in order to reach the desired effect that the poet aspires to. His poetry was characterized by stylistic and artistic characteristics that have their stylistic uniqueness Poetry, free poetry was the beautiful poetry that captures the reader’s being, so what attracted him most and drew his attention were those creative initiations in which Al-Sayyab showed his ability to control the tools and formulas of language with ideas that reflect his ability to bring about the paradox between the modernShaker al-Sayyab, as his initiation was distinguished by a distinctive artistic structure, including his poetic beginning with a descriptive temporal and spatial structure. We also dealt with the study of the patterns of initiation in al-Sayyab's poetry, as we talked about the long initiation, the focused initiation, and The conclusion dealt with the most important findings of the research.
Keywords: Inception, artistry, structure